2015
DOI: 10.1039/c5tb00247h
|View full text |Cite
|
Sign up to set email alerts
|

A toolkit for bioimaging using near-infrared AgInS2/ZnS quantum dots

Abstract: Cadmium free near-infrared AgInS2/ZnS quantum dots have been synthesized and used for imaging the microenvironment of cancer tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…Recently, I 2 -VI, III-V and I-III-VI 2 semiconductors have emerged as candidate materials for cadmiumfree QDs, [1][2][3] and they are usable in a variety of applications, including photovoltaics, [4][5][6] light-emitting devices, 1,7-10 and bioimaging. 3,[11][12][13] The emission color of these QDs can be engineered by tuning their bandgap energy (E g ) via their size; this is one of the unique characteristics of QDs, which is referred to as the quantum size effect. [14][15][16] Furthermore, the bandgaps of I-III-VI 2 semiconductors, a group that includes silver indium sulde (AgInS 2 ), copper indium sulde (CuInS 2 ), and their selenide derivatives, can also be controlled by adjusting their chemical composition and creating alloys from these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, I 2 -VI, III-V and I-III-VI 2 semiconductors have emerged as candidate materials for cadmiumfree QDs, [1][2][3] and they are usable in a variety of applications, including photovoltaics, [4][5][6] light-emitting devices, 1,7-10 and bioimaging. 3,[11][12][13] The emission color of these QDs can be engineered by tuning their bandgap energy (E g ) via their size; this is one of the unique characteristics of QDs, which is referred to as the quantum size effect. [14][15][16] Furthermore, the bandgaps of I-III-VI 2 semiconductors, a group that includes silver indium sulde (AgInS 2 ), copper indium sulde (CuInS 2 ), and their selenide derivatives, can also be controlled by adjusting their chemical composition and creating alloys from these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the NP-containing assemblies are produced using microball-like polymer macromolecules capable of binding to the NP surface (for example polyethylene glycol [3,5,6,[9][10][11], phospholipids [12,13], various block-copolymers, DNAs, etc. [3,5]).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, big expectations are associated with ternary indium-based chalcopyrites [1,19,20], such as CuInS 2 and CuInS 2 /ZnS NPs [13][14][15][16]20], non-stoichiometric Cu-In-S [20,21] and Ag-In-S NPs [10], CuInS x Se 2-x NPs [22], AgInS 2 and AgInS 2 /ZnS NPs [9,11,23,24] that can also be produced by the well-known "hot injection" methods with the PL QY reaching 40-65% [1,14,21,22]. Such compounds combine a series of very attractive features, including relatively low toxicity and ability to preserve chalcopyrite structure in a broad range of NP sizes and non-stoichiometries [1,19,20,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is vital to develop other types of QDs with reduced toxicity. Several QD toxicity studies have addressed and reduced in vivo toxicity by coating the cadmium-based core with another material [19,20]. However, a study with nonhuman primates revealed that most of the initial dose of cadmium still remained in the liver, spleen, and kidneys 90 days after injection [21].…”
Section: Introductionmentioning
confidence: 99%